Perancangan Sistem Aplikasi Support Ticketing Berbasis Web pada PT ABCD - Christina, Selly; Ziveria , Mira (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
PT ABCD is one of the big companies based in Jakarta. PT ABCD has several branches in several cities. PT ABCD uses Information Technology to run operational activities more effectively. But in these activities, various departments also experience problems caused by user errors or system bugs. Therefore, the IT team has a helpdesk division that functions as the first person to be contacted if users experience problems. To make reports of problems experienced by users more effectively, a web-based support ticketing application is designed. The function of the application is that reporting can be done so that it can be reported to superiors and this incident does not occur if the same incident occurs with the helpdesk team knowing what the solution is. Intisari: Web, helpdesk, ticketing, IT.